Selective neutralisation and deterring of cockroaches with laser automated by machine vision. (3rd April 2023) - Rakhmatulin, Ildar; Lihoreau, Mathieu; Pueyo, Jose
ABSTRACT: Controlling insect pests still relies on the extensive usage of generic and established methods, such as pesticides, which utilise broad spectrum chemicals or toxins persisting in the environment and targeting non-pest insect species. Therefore, more effective and environmental friendly approaches are needed to counteract these damaging effects. Since a laser can be remotely directed to neutralise undesirable targets, this approach could be highly promising for controlling insect pests in a selective and ecofriendly fashion. In this study, we present a laser system automated by machine vision for neutralising and influencing the behaviour of insect pests. By performing experiments on domiciliary cockroaches, Blattella germanica, we demonstrate that our approach enables the immediate and selective neutralisation of individual insects at a distance up to 1.2 m. We further show the possibility to deter cockroaches by training them not to hide under a dark shelter through aversive heat conditioning with a low power-laser. Parameters of our prototype system can readily be tuned for applications in various situations and on different pest species like mosquitoes, locusts, and caterpillars. The prospect of this study is to pursue the creation of a standalone, safe for the environment, compact, low-cost, and energy-efficient device system for pest control.